An integrated evaluation of some faecal indicator bacteria (FIB) and chemical markers as potential tools for monitoring sewage contamination in subtropical estuaries. (April 2018) - Cabral, Ana Caroline; Stark, Jonathan S.; Kolm, Hedda E.; Martins, César C.
Abstract: Sewage input and the relationship between chemical markers (linear alkylbenzenes and coprostanol) and fecal indicator bacteria (FIB, Escherichia coli and enterococci), were evaluated in order to establish thresholds values for chemical markers in suspended particulate matter (SPM) as indicators of sewage contamination in two subtropical estuaries in South Atlantic Brazil. Both chemical markers presented no linear relationship with FIB due to high spatial microbiological variability, however, microbiological water quality was related to coprostanol values when analyzed by logistic regression, indicating that linear models may not be the best representation of the relationship between both classes of indicators. Logistic regression was performed with all data and separately for two sampling seasons, using 800 and 100 MPN 100 mL −1 of E. coli and enterococci, respectively, as the microbiological limits of sewage contamination. Threshold values of coprostanol varied depending on the FIB and season, ranging between 1.00 and 2.23 μg g −1 SPM. The range of threshold values of coprostanol for SPM are relatively higher and more variable than those suggested in literature for sediments (0.10–0.50 μg g −1 ), probably due to higher concentration of coprostanol in SPM than in sediment. Temperature may affect the relationship between microbiological indicators and coprostanol, since the threshold value of coprostanol found here was similar to tropical areas, but lower than those found during winter in temperate areas, reinforcing the idea that threshold values should be calibrated for different climatic conditions. Graphical abstract: Image 1 Highlights: LABs and coprostanol levels were determined on suspended particulate matter. Logistic regression was used to analyze relationships between sewage indicators. Coprostanol predicted microbiological water quality with 80% accuracy. Coprostanol threshold level of unsafe sewage input was 1.00–2.23 μg g −1 SPM. Abstract : Coprostanol levels present in estuarine suspended particulate matter can be used to predict microbiological water quality, when analyzed by logistic regression.